Refractive lens exchange in modern practice: when and when not to do it? - Alió, Jorge L (Eye Vis (Lond), 2014)
Cataract surgery due to advances in small incision surgery evolved from a procedure concerned with the primary focus on the safe removal of cataractous lens to a procedure focused on the best possible postoperative refractive result. As the outcomes of cataract surgery became better, the use of lens surgery as a refractive modality in patients without cataracts has increased in interest and in popularity. Removal of the crystalline lens for refractive purposes or refractive lens exchange (RLE) presents several advantages over corneal refractive surgery. Patients with high degrees of myopia, hyperopia and astigmatism are still not good candidates for laser surgery. Moreover, presbyopia can currently only be corrected with monovision or reading spectacles. RLE supplemented with multifocal or accommodating intraocular lenses (IOLs) in combination with corneal astigmatic procedures might address all refractive errors including presbyopia, and eliminate the future need for cataract surgery.